Subjective and Objective Evaluation of Brazilian Portuguese TTS Voice Font Quality - Daniela Braga; Luis Pinto Coelho; Dias, J. (Proc AST 2007, 14th International Workshop on Advances in Speech Technology, Maribor, Slovenia, 2007)
In this paper, it is our aim to define a set of objective acoustic criteria, based on subjective listeners assessment of talent voices, that can help to rate the voice font quality, bearing in mind the development of Text-to-Speech systems (hereafter TTS). The voice talent selection process is seldom discussed in scientific papers, since academic community is obviously more concerned with synthetic voice evaluation than with modal voice talent assessment. However, the choice of a voice that will be used in TTS systems is definitely of extreme importance. In this work, we describe the selection process of the Brazilian Portuguese voice talent, based on socio and linguistic criteria and supported by subjective and objective tests and measurements of modal voice quality. Relationship between subjective and objective parameters is presented and discussed. A subjective test comparing natural and resynthesized voices was also conducted and its results are discussed